Labour Law Utopias: Post-Growth and Post-Productive Work Approaches - Nicolas Bueno; Beryl ter Haar; Nuna Zekić (Oxford University Press, 2024)
Labour Law Utopias: Post-Growth and Post-Productive Work Approaches engages with new socioeconomic ideas, or utopias, that look beyond the current growth-driven competitive market economy. Building on critiques of economic growth and the limits of the logic of human productivity and competitivity for workers and the planet, it explores alternative approaches and what they mean for work in general and labour law in particular. The concept of post-growth is used to rethink the purpose of the economy by looking beyond merely increasing wealth, consumption, and production. Post-productive work is introduced to question the centrality of economically productive work in labour law. The chapters in this book adopt a forward-looking approach and discuss whether and how labour law can contribute to emancipation from the constraints of growth and productivity by revisiting the value, organization, and impact of work on people and the environment.
Keywords: 340; Post-growth; economic growth; productive work; labour law; wellbeing; ecological labour law; care work; climate change; basic income